Antimicrobial resistant Escherichia coli in Scottish wild deer: Prevalence and risk factors. (1st December 2022) - Elsby, Derek T.; Zadoks, Ruth N.; Boyd, Kenneth; Silva, Nuno; Chase-Topping, Margo; Mitchel, Mairi C.; Currie, Carol; Taggart, Mark A.
Abstract: Antimicrobial resistance (AMR) is a recognised threat to global health. Obtaining data on the prevalence of AMR in environmental bacteria is key to understanding drivers and routes of transmission. Here, 325 Shiga toxin negative deer faecal samples—gathered from across the Scottish mainland—were screened for the presence of AMR Escherichia coli and investigated for potential risk factors associated with AMR occurrence. E. coli with resistance to antimicrobials of clinical health concern, including carbapenems and 3rd generation cephalosporins, were targeted. Ninety-nine percent of samples yielded E. coli, and the prevalence of resistant E. coli at the level of faecal samples was 21.8% (n = 71) for tetracycline, 6.5% (n = 21) for cefpodoxime, 0.3% for ciprofloxacin (n = 1), with no recorded resistance to meropenem. Potential risk factors for tetracycline and cefpodoxime resistance were investigated. The presence of broadleaved woodlands was significantly associated with both AMR phenotypes, which may relate to land use within or around such woodlands. Associated risk factors varied across resistance phenotype and deer species, with proximity or density of horses an indicator of significantly decreased and increased risk, respectively, or tetracycline and cefpodoxime resistance in E. coli from roe deer, but not from red deer. Distance from wastewater treatment plants was a significant risk factor for tetracycline resistance in E. coli from red deer but not from roe deer. Data indicated that AMR E. coli can occur in wild deer populations that are not directly exposed to the selective pressure exerted by antimicrobial treatment. Overall, resistance to critically important antimicrobials was found to be low in the studied population, suggesting no immediate cause for concern regarding human health. Utilising existing culling frameworks, wild deer in Scotland could function well as a sentinel species for the surveillance of AMR in the Scottish environment. Graphical abstract: Image 1 Highlights: Baseline of antimicrobial resistance in Scottish wild deer was established. Whole faecal sample screening of wild deer faeces for resistant E. coli . Low or no detectable levels of resistance to critically important antimicrobials. Resistance associated with broadleaved woodlands, but varies by deer species. Existing culling framework could facilitate nationwide surveillance of resistance.